The role of the central banker today : lecture delivered by Louis Rasminsky, Governor, Bank of Canada - Rasminsky, Louis; Siglienti, Stefano (Rome : The PerJacobson Foundation, 1966)
This paper contains the text of papers given in Rome on November 9, 1966.
osc 27/9/2017
Loans
Keywords: Banks and banking, Central